Critical parameters and pair correlations in confined multicomponent liquids - A.N.Vasil'ev (Condensed Matter Physics, 2006)
We investigate multicomponent finite-size liquid systems with geometry of plane-parallel layer and cylinder. We consider these systems are being affected by weak external field which causes their anisotropy. For these systems we find pair correlation functions and analyze the effect of space limitation and external field on correlative behaviour of multicomponent liquid. We compare our results with the data for simple and binary finite-size systems.